2018
DOI: 10.1590/1516-3180.2018.0050170418
|View full text |Cite
|
Sign up to set email alerts
|

Incorrect use of inhalation devices among patients with bronchial asthma. A hospital-based cross-sectional study in Rio de Janeiro, Brazil

Abstract: Less than half of the sample performed the inhalation technique correctly. Incorrect inhalation technique was related to lower number of evaluations of the use of the inhalation device and uncontrolled asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Previous studies found that patient age, gender, educational status, the duration of disease, the type of inhaler device, correct inhalation technique, and the use of multiple devices, all played a role in the effectiveness of the drugs used by inhalation. 9 , 10 , 11 , 12 , 13 Although old age was considered as a risk factor for inhaler misuse, specific data pertaining to this issue were debatable. 13 Young patients can be expected to use inhaler devices or any other medications more accurately due to higher levels of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that patient age, gender, educational status, the duration of disease, the type of inhaler device, correct inhalation technique, and the use of multiple devices, all played a role in the effectiveness of the drugs used by inhalation. 9 , 10 , 11 , 12 , 13 Although old age was considered as a risk factor for inhaler misuse, specific data pertaining to this issue were debatable. 13 Young patients can be expected to use inhaler devices or any other medications more accurately due to higher levels of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…found that inhaler misuse was higher in patients older than 50 years-of-age, but without a statistically significant difference. 10 Furthermore, a recent systematic review showed that patients who were older and younger than 65 years significantly misused their inhalers; in addition, they made the same types of mistakes. 11 In contrast, we found that the rate of misuse was higher in patients older than 60 years-of-age.…”
Section: Discussionmentioning
confidence: 99%
“…A presente revisão constatou que há falhas na execução da técnica inalatória em pacientes com asma e DPOC, além disso considera-se uma forte relação da eficácia do tratamento, incluindo melhora do quadro clínico e parâmetros laboratoriais, e o uso correto do dispositivo inalatório (PESSÔA et. al, 2018).…”
Section: Discussionunclassified
“…Estudos prévios demonstram que o tempo de tratamento não influencia na técnica, mas sim a orientação e avaliação do médico. A não orientação, bem como, a orientação insuficiente tem sido relacionada como principal e único fator para o uso inadequado dos dispositivos inalatórios (PESSÔA et al, 2018).…”
Section: Introductionunclassified
“…The incorrect use of inhalation devices is influenced by multiple factors, such as patient-related factors (eg, age, gender, or education level) and medicine-related factors (eg, type of inhalation device, duration of drug use, or inhalation device use instruction). 9 , 10 Given so many associated risk factors, an accurate predictive tool to detect such populations and provide early interventions may be the simplest and most effective action against the incorrect use of inhalation devices. A predictive nomogram may make a difference for patients with chronic airway diseases who present improper inhalation techniques.…”
Section: Introductionmentioning
confidence: 99%